2017
DOI: 10.12973/eu-jer.6.4.565
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Teachers! The Impact of Mindfulness Training on Self-Regulation and Classroom Performance in a Sample of German School Teachers

Abstract: Abstract:Teacher wellbeing and performance is affected by their ability to cope with the demands of the profession. This pilot nonrandomized, waitlist-controlled study investigated the impact of a mindfulness intervention (Mindfulness-Based Stress Reduction) on teachers' wellbeing, self-regulation ability and classroom performance applying a mixed-method design. The sample was comprised of 32 German school teachers (93% female) which were distributed to a control and intervention group. Compared to the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 53 publications
(47 reference statements)
1
26
0
6
Order By: Relevance
“…Mindfulness practices that are done by leaders are ethics-a training that bridges all differences. Mindfulness is a state of mind that most people can attain, but to maintain it for more extended periods, it needs practicing, for example, through mindfulness meditation (Rupprecht, 2017). The first function is connecting everyone.…”
Section: He Can Be a Bridge To Like A Keep Information From The Brmentioning
confidence: 99%
“…Mindfulness practices that are done by leaders are ethics-a training that bridges all differences. Mindfulness is a state of mind that most people can attain, but to maintain it for more extended periods, it needs practicing, for example, through mindfulness meditation (Rupprecht, 2017). The first function is connecting everyone.…”
Section: He Can Be a Bridge To Like A Keep Information From The Brmentioning
confidence: 99%
“…Concernant notre deuxième objectif complémentaire (Tableau 5), les corrélations rencontrées entre l'augmentation des scores de mindfulness et les améliorations observées pour chacune des sept autres variables en pré-/post-intervention, puis amplifiées pour six d'entre elles en pré-/suivi à deux mois, rejoignent les résultats de la littérature stipulant que l'accroissement des dispositions en mindfulness joue le rôle d'un « mécanisme » central dans les bienfaits procurés par les MBIs [17,31,47,104,105,110].…”
Section: Discussionunclassified
“…Malgré la petite taille des échantillons, cette étude est l'une des premières à montrer l'effet bénéfique d'une intervention MBI à la fois sur la santé des enseignants et sur l'organisation même de la classe. Une récente étude a été conduite par Rupprecht, Paulus et Walach en Allemagne sur 32 enseignants d'écoles primaires et secondaires sur le format MBSR, publiée en 2017 [105], avec des résultats proches de ceux de Flook (2013) et de Roeser (2013) [94,104] : l'entraînement à la mindfulness, mesuré sur l'échelle FMI-14 (Freiburg Mindfulness Inventory) créée par Walach et al [106], diminue les symptômes liés au stress avec des améliorations sur les mesures de stress, santé générale (GHQ-12), capacités de coping face aux exigences professionnelles (AVEM), régulation émotionnelle et auto-efficacité. Les trois auteurs observent en revanche une diminution de l'engagement professionnel des enseignants.…”
Section: La Pleine Conscience Et Son Application Au Champ éDucatifunclassified
See 1 more Smart Citation
“…The benefits of the mindfulness have been proven with numerous research. For instance, research has found that mindfulness is related with self-regulation (Brown & Ryan, 2003;Bishop et al, 2004;Rupprecht, Paulus, & Walach, 2017); emotion regulation (Bao, Xue, & Kong, 2015;Cenkseven Onder & Utkan, 2018;Uygur, 2017); empathy (Pepping & Halford, 2016;Pratscher et al, 2019); stress (Bao et al, 2015;Cenkseven Onder & Utkan, 2018;Chu, 2010;Kabat-Zinn, 2005;Neece, 2014), and anxiety (Goodman et al, 2014;Guardino, Dunkel Schetter, Bower, Lu, & Smalley, 2014;Vieten & Astin, 2008). It can be seen that most of the studies in the literature, which focus on the subject, examine mindfulness as experienced through individuals' inner experiences (Frank, Jennings, & Greenberg, 2016).…”
Section: Introductionmentioning
confidence: 99%